Negotiation - Rau, Alan Scott (Foundation Press, 2006)
This book is about the ways in which those" in charge" of "doing something about dispute" help to resolve those disputes. In particular, it is about the choices that lawyers make in helping to"put at rest" the disputes in which their clients have become involved,...